Про деякі особливості щодо віктимної поведінки жертв корисливо-насильницьких злочинів - Мірошніченко, Т. О.; Miroshnichenko, T. O. (Вісник Харківського національного університету внутрішніх справ. - 2015. - № 1 (68). - С. 88-95., 2015)
Проаналізовано окремі наукові підходи до визначення типів поведінки жертв корисливо-насильницьких злочинів. Окреслено гендерні, соціальні, вікові групи потенційних жертв, сформульовано власний погляд на поділ жертв на групи. Визначено окремі причини та обставини індивідуальної віктимності жертви.

Various qualities and features of people in different ways can affect the increase or decrease of victimization of a person. Studying the causes of human victim behavior, it is necessary first of all to pay attention to the psychological characteristics of a victim’s personality. Analysis of some scientific approaches to determine the types of victims’ behavior of selfish and violent crimes has indicated that the behavior of the victim of selfish and violent crimes may be varied: neutral, positive and negative. For example, at the time of the crime commission, most victims are actively trying to resist the attacker, and almost a third of the victims do not do anything for criminal obstruction. By the results of research the author has formulated his own division of victims of selfish and violent crimes into following groups: «provocative» victims, «frivolous» victims, «reckless» victims, «gullible» victims, «neutral» victims. This classification is the basic for further study of the types of victims of selfish and violent crimes by the author. It is determined that the victims of selfish and violent crimes are different categories of persons by age, sex, social status, professional direction. The above crimes have common features by goals, motives, objects of attack and threats of using both physical and psychological violence. Based on the research of domestic and foreign scientists’ works, it is concluded about peculiarities of individual victimization of selfish and violent crimes’ aggrieved persons, which is associated with personal qualities of a future victim.

Проанализированы отдельные научные подходы для определения типов поведения жертв корыстно-насильственных преступлений. Очерчены гендерные, социальные, возрастные группы потенциальных жертв, сформулирован собственный взгляд на разделение жертв на группы. Определены отдельные причины и обстоятельства индивидуальной виктимности жертвы.
Miroshnichenko, T.O. (2015), “On some specifics concerning victim behavior of selfish and violent crimes’ aggrieved persons” [“Pro deiaki osoblyvosti shchodo viktymnoi povedinky zhertv koryslyvo-nasylnytskykh zlochyniv”], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 1, pp. 88-94.
Мірошніченко, Т. О. Про деякі особливості щодо віктимної поведінки жертв корисливо-насильницьких злочинів // Вісник Харківського національного університету внутрішніх справ. - 2015. - № 1 (68). - С. 88-95.
Keywords: Наукові публікації. Scientific publications. Научные публикации; Кримінологія. Criminology. Криминология; victim behavior; виктимное поведение; віктимна поведінка; victim; types of victims; aggrieved person; selfish and violent crimes; individual victimization; жертва; типы жертв; потерпевший; корыстно-насильственные преступления; индивидуальная виктимность; типи жертв; потерпілий; корисливо-насильницькі злочини; індивідуальна віктимність